The Role Of Hindu Family In Shaping The Character Of Suputra Children - Ni Wayan Sumertini (Kamaya: Jurnal Ilmu Agama, 2023)
Religious education seeks to shape the character of children. The role of the family in shaping the character of young generation children becomes essential. The primary and first education is done in the family environment. The lack of ethical education and character in the family environment causes the learners' personalities to deviate from the norms and ethics in the community; teaching in the family sector, schools, and society becomes the determinant in the character formation of children. This research finds some results: first, the pattern of guidance of character in Hindu family environment to form the personality and character of Hindu children, to form the character of child suputra. Ways of tolerance and tolerance in the Hindu family shape the character of suputra children. The pattern of disciplinary attitude building for Hindu children, children in Hindu family environments are familiarized with high discipline attitude. Second, obstacles are faced in shaping the character of children's suputra as the internal and external factors of family. Family families are less harmonious, and promiscuity is the cause of less optimal education in the family environment to form the character of children suputra. Third is the effort to provide education value tattwa, value susila, the value of the upacara, aesthetic value, and the existence of education and training in pasraman to pursue character education.